2014
DOI: 10.3171/2014.2.spine13672
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole effects on behavioral sensitivity and the development of axonal damage and spinal modifications that occur after painful nerve root compression

Abstract: Object Cervical radiculopathy is often attributed to cervical nerve root injury, which induces extensive degeneration and reduced axonal flow in primary afferents. Riluzole inhibits neuro-excitotoxicity in animal models of neural injury. The authors undertook this study to evaluate the antinociceptive and neuroprotective properties of riluzole in a rat model of painful nerve root compression. Methods A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 75 publications
(144 reference statements)
2
46
0
Order By: Relevance
“…Compression of the right C7 dorsal nerve root was performed using procedures described previously [19], [20]. Briefly, rats were anesthetized with inhaled isoflurane (4% for induction, 2-3% for maintenance), and placed in a prone position.…”
Section: B Painful Cervical Nerve Root Compressionmentioning
confidence: 99%
“…Compression of the right C7 dorsal nerve root was performed using procedures described previously [19], [20]. Briefly, rats were anesthetized with inhaled isoflurane (4% for induction, 2-3% for maintenance), and placed in a prone position.…”
Section: B Painful Cervical Nerve Root Compressionmentioning
confidence: 99%
“…[9] Several animal models of nerve root compression have shown that even a transient, 15-minute compression applied to the nerve root is sufficient to induce sustained pain. [10, 11] In addition to pain, axonal damage and myelin degeneration are evident in the nerve root by 7 days after compression. [11] Such damage is hypothesized to relate to and cause neuronal dysfunction and contribute to the maintenance of pain by impaired axonal transport in the nerve root and disrupting the afferent signals that communicate to synapses in the spinal cord dorsal horn.…”
mentioning
confidence: 99%
“…[40] In this study, administration of the SOD-loaded porous polymersomes partially prevented the axonal damage and disorganization (Figure 3c) that usually occurs after painful nerve root compression. [11] Treatment with the empty polymersomes exhibited the most disruption in NF200 labeling and axonal thinning, while treatment with both free SOD regiments displayed axonal damage to a lesser extent, suggesting that free SOD antioxidant treatment administration may delay the onset of pain, but alone may not sufficiently reduce ROS to rescue neuronal health after injury. The prevention of axonal damage with SOD-loaded porous polymersomes also suggests that these polymersomes may have greater antioxidant activity than free antioxidant alone, especially since it is known that free antioxidants are rapidly degraded in-vivo.…”
mentioning
confidence: 99%
“…Thermal hypersensitivity was measured following mechanical assessment using a commercially available device (UC San Diego) and customary methods [25]. After acclimation to the apparatus for 30 minutes, the withdrawal latency for each rat was averaged across forepaws over three testing rounds on each day; baseline measurements were averaged over two days before injections.…”
Section: Methodsmentioning
confidence: 99%